2020
DOI: 10.1016/s2213-2600(20)30066-7
|View full text |Cite
|
Sign up to set email alerts
|

Protecting health-care workers from subclinical coronavirus infection

Abstract: Protecting health-care workers from subclinical coronavirus infectionHealth-care workers face an elevated risk of exposure to infectious diseases, including the novel coronavirus in China. It is imperative to ensure the safety of healthcare workers not only to safeguard continuous patient care but also to ensure they do not transmit the virus. COVID-19 can spread via cough or respiratory droplets, contact with bodily fluids, or from contaminated surfaces. 1 According to recent guidelines from the China Nation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
527
1
39

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(572 citation statements)
references
References 2 publications
5
527
1
39
Order By: Relevance
“…It found the mean R 0 to be 3. 28 and median R 0 to be 2.79, which exceeds the WHO preliminary R 0 of 1.4-2.5 (average 1.95). 24 Models using stochastic and statistical methods, such as exponential growth were reasonably comparable, while mathematical methods produced estimates on the higher side.…”
Section: Transmissioncontrasting
confidence: 52%
“…It found the mean R 0 to be 3. 28 and median R 0 to be 2.79, which exceeds the WHO preliminary R 0 of 1.4-2.5 (average 1.95). 24 Models using stochastic and statistical methods, such as exponential growth were reasonably comparable, while mathematical methods produced estimates on the higher side.…”
Section: Transmissioncontrasting
confidence: 52%
“…Globally, until 28 th February 2020 there have been reported 83,774 confirmed cases and 2,867 deaths [2]. During the periods of outbreak of COVID-19 or other infectious diseases, implementations of infection prevention and control (IPC) becomes a great importance in healthcare settings [3], particularly the great importance of personal protection of healthcare workers [4]. In order to contain the outbreak of COVID-19 in Mainland China, National Health Commission of the People's Republic of China (NHCPRC) have so far dispatched medical support teams (41,600 healthcare workers from 30 provinces and municipalities) to support the medical treatment in Wuhan and Hubei province [5].…”
Section: Exploring the Reasons For Healthcare Workers Infected With Nmentioning
confidence: 99%
“…In early January, he contracted COVID-19 from an asymptomatic glaucoma patient and succumbed to the disease one month later [10]. There were anecdotal reports suggesting that individuals may be infected by patients with subclinical infection [11], either by droplets or by direct contact with secretions from infected cases followed by subsequent inoculation into mucous membranes. Anecdotal reports suggested that when no eye protection was worn, the virus could also possibly be transmitted by aerosol contact with conjunctiva and cause infection [12][13][14].…”
Section: The Risks Of Covid-19 To Ophthalmologists and Patientsmentioning
confidence: 99%
“…With a daily attendance of over 500 patients in our outpatient clinic, it is important to reduce the number of outpatient attendance to prevent cross-infection in this vulnerable group of patients, as it has been shown that even subclinical patients are capable of transmitting the virus [11]. Informing a large number of outpatients to reschedule their appointments is often challenging.…”
Section: Lowering Patient Attendance and Suspension Of Elective Clinimentioning
confidence: 99%